LAN Network Optimization to Support Practicum Activities Using Action Research Method at STMIK Jayakarta - Fendi Alviyanto; Thomas Budiman; Anton Zulkarnain Sianipar (Jurnal Indonesia Sosial Teknologi, 2024)
The importance of using computer networks in campus laboratories to improve the quality of education and research is also increasing. However, there are problems found in the use of computer networks in campus laboratories, namely low data transmission speeds, network insecurity and inaccessible resources. Therefore, this research was conducted to determine the factors that influence the performance of computer networks in campus laboratories, including data transmission speed. Computer networks evolved from point-to-point communication to computers connecting to each other and exchanging information. The research methodology involves experimental data being tested, for example the effect of communication speed on computer network performance in campus laboratories.